2015
DOI: 10.1371/journal.pone.0142786
|View full text |Cite|
|
Sign up to set email alerts
|

Zonisamide Enhances Neurite Elongation of Primary Motor Neurons and Facilitates Peripheral Nerve Regeneration In Vitro and in a Mouse Model

Abstract: No clinically applicable drug is currently available to enhance neurite elongation after nerve injury. To identify a clinically applicable drug, we screened pre-approved drugs for neurite elongation in the motor neuron-like NSC34 cells. We found that zonisamide, an anti-epileptic and anti-Parkinson’s disease drug, promoted neurite elongation in cultured primary motor neurons and NSC34 cells in a concentration-dependent manner. The neurite-scratch assay revealed that zonisamide enhanced neurite regeneration. Zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…44 In addition to the antioxidant effects, it was also shown that ZNS has the ability to promote neurite elongation in mouse primary motor neurons in a dosedependent manner. 38 In this study, we found that the axon lengths of neurons were obviously elongated in the ZNS and (Figure 7). Enhanced neurite elongation in primary motor neurons and axonal regeneration may partially account for the enhancements of BDNF and Ntrk2 by ZNS, 38 although the underlying mechanisms remain unknown.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…44 In addition to the antioxidant effects, it was also shown that ZNS has the ability to promote neurite elongation in mouse primary motor neurons in a dosedependent manner. 38 In this study, we found that the axon lengths of neurons were obviously elongated in the ZNS and (Figure 7). Enhanced neurite elongation in primary motor neurons and axonal regeneration may partially account for the enhancements of BDNF and Ntrk2 by ZNS, 38 although the underlying mechanisms remain unknown.…”
mentioning
confidence: 50%
“…38 In this study, we found that the axon lengths of neurons were obviously elongated in the ZNS and (Figure 7). Enhanced neurite elongation in primary motor neurons and axonal regeneration may partially account for the enhancements of BDNF and Ntrk2 by ZNS, 38 although the underlying mechanisms remain unknown.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…17 In addition, zonisamide has other pharmacological effects, including neuroprotective effects in dopaminergic neurons, 18 neuroprotection against cerebral ischemia, 19 free radical scavenging activities 2021 and protective effects against oxidative stress-induced cell death in primary motor neurons. 22 The findings of the present study suggest that antioxidant effects might induce neuroprotective effects, with regard to increasing levels of urinary 8-OHdG in PD. These results feature several limitations, particularly as the majority of patients received a combination of drugs.…”
Section: Discussionmentioning
confidence: 48%
“…Although zonisamide has been globally prescribed for the treatment of epilepsy, it is also an effective antiparkinsonian agent, especially for resting tremor, in Japan . In addition, zonisamide has other pharmacological effects, including neuroprotective effects in dopaminergic neurons, neuroprotection against cerebral ischemia, free radical scavenging activities and protective effects against oxidative stress‐induced cell death in primary motor neurons . The findings of the present study suggest that anti‐oxidant effects might induce neuroprotective effects, with regard to increasing levels of urinary 8‐OHdG in PD.…”
Section: Discussionmentioning
confidence: 99%